Chitosan-zinc oxide composite for active food packaging Applications - Abdul Razak, S.R.; Basri, Hatijah (Science Publishing Corporation, 2018)
Chitosan-zinc oxide (C-ZnO) films were prepared by a simple one pot procedure. In order to investigate the property of C-ZnO films, two composite films were prepared by varying the loading of ZnO and compared with pure chitosan film (C). The films were character-ized by various techniques such as FTIR, DSC, tensile, contact angle and water vapour permeability. FTIR analysis showed changes in hydrogen bonds band at 3351 cm-1 compared to pure chitosan film. The incorporation of ZnO in chitosan films increased the contact angle by 30.5% in C-ZnO1.0 film while water vapour transmission rate decreased by 7.8% compared to C film. From the tensile test, C-ZnO0.5 and C-ZnO1.0 films were found to be much superior by 1.5 times and 2.5 times respectively compared to bare chitosan film. Larger inhibition ring (by 47%) was exhibited by C-ZnO1.0 as compared to C-ZnO0.5 when tested against S.aureus. From the results, it is displayed that the incorporation of zinc oxide to chitosan improve their properties which also shown the potential to become a candi-date for food active packaging.